Design of CW THz PhotonicTtransmitter based on Low Pass-Filter and Bow-tie Wideband Antenna - Ibtissame Moumane; J. Zbitou; M. Latrach; A. Errkik; O. Chakkor; A. Fouad (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper presents the design of Continuous Wave Terahertz photonic transmitters which is composed from photodetector (PD) associated to a wideband antenna, low–pass filter (LPF) and DC Probe. Firstly, we have developed the bow-tie wideband antenna using an EM solver Momentum integrated in ADS “Advanced Design System”. Then we had optimized a low-pass filter which is responsible of blocking the RF signal providing from the antenna to reach the DC probe. And finally, we have validated into simulation the CW THz photonic transmitter. The three structures are based on multi-layers GaAs substrate, which is the most widely used for THz circuit design. The dimensions of the Whole circuit are 776.788 × 303.39〖μm〗^2.